To solve the system of equations using substitution, we can start with the two given equations:
- \( y = 2 + 3x \)
- \( 4x - 3y = -16 \)
First, substitute the expression for \( y \) from the first equation into the second equation.
Substituting \( y \) in the second equation:
\[ 4x - 3(2 + 3x) = -16 \]
Now, simplify the left side:
\[ 4x - 6 - 9x = -16 \]
Combine like terms:
\[ -5x - 6 = -16 \]
Now, add 6 to both sides:
\[ -5x = -10 \]
Next, divide both sides by -5:
\[ x = 2 \]
Now that we have the value of \( x \), substitute it back into the first equation to find \( y \):
\[ y = 2 + 3(2) = 2 + 6 = 8 \]
Thus, the solution to the system of equations is \( (x, y) = (2, 8) \).
Therefore, the correct answer is:
(2, 8)